MENINGKATKAN KEMAMPUAN BEREMPATI ANAK USIA 5-6 TAHUN MELALUI COOPERATIVE LEARNING - Fitri Wulandari Sukmady (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2017)
The capacity for empathy is the ability to know the feelings of others. Empathy is built on self-awareness, the child opens the emotions themselves more skilled also children can ‘understanding other people’s feelings. The ability to empathize 5-6 years old children in early childhood Islamic Bina Bangsa School, Serang - Banten still low, this can be seen from the attitude of everyday habits of school children who have not been able to demonstrate an understanding of the feelings of their peers. This occurs because the learning method has not been able to give an understanding to the children about how to act and interact with friends. Hence the need for the implementation of cooperative learning that can stimulate cooperation and raise children against child interaction that produces a good ability to empathize. The method used in this study is action research methods, measures designed in a repeating cycle, in this study consisted of two cycles. In the first cycle of 8 times the action and the second cycle 2 times the action, with a 70% success criteria. Subjects in this study were 11 children aged 5-6 years consisting of 3 boys and 8 girls in early childhood Bina Bangsa School Islamic School, Serang - Banten. In each cycle consists of three stages: planning, action and observation carried out simultaneously, observation, and the last reflection. The technique of collecting data through observation, field notes, interview notes and documentation. Analysis of data using data reduction, data presentation, and conclusion. Stages in the research process is the first to design and implement cooperative learning RPPH in learning. Based on the results obtained that the ability to empathize with children aged 5-6 years through cooperative learning with the results of this research note that the 28,29% initial conditions later in the first cycle increased to 50,43%, in the second cycle has increased significantly to 96,42% and having success on the indicators that have been targeted. Based on the results of data that has been obtained, it can be concluded that with the implementation of cooperative learning can improve the ability to empathize 5-6 years old children in early childhood Islamic Bina Bangsa School, Serang - Banten.